ANALISIS KUALITAS PELAYANAN PUBLIK PADA DINAS PERTANIAN TANAMAN PANGAN DAN HORTIKULTURA KABUPATEN KERINCI - Julianto, Pebi (Qawwam : The Leader's Writing, 2023)
This study aims to describe the quality of public services at the Agricultural Extension Office (BPP) in Airwarm District, Kerinci Regency. This research is a descriptive study using a qualitative approach. Data collection techniques were carried out by observation, interviews, and documentation techniques. Research informants were determined using a purposive sampling technique. The informants in this study were BPP office employees and 3 farmer group leaders and 2 farmer group members as supporting informants. The data analysis technique used is divided into several stages, namely data reduction, data presentation, and drawing conclusions. While checking the validity of the data is done by triangulation of data sources and methods. This study shows the quality of public services at the office of the agricultural extension service center in Airwarm District, Kerinci Regency. assessed from the dimensions of physical evidence (tangible), reliability (reliability), responsiveness (responsiveness). Based on (1) physical evidence (tangible) dimensions, service support facilities satisfy the community but it requires expansion of farmer group members because the land is still large. (2) the dimension of reliability, employees perform services in accordance with procedures, (3) responsiveness, the response or responsiveness of extension agents is not fully good because there are extension officers working in designated areas who do not mingle with farmers due to the rare the extension worker went down the field.